2015
DOI: 10.1111/obr.12354
|View full text |Cite
|
Sign up to set email alerts
|

Food cue reactivity and craving predict eating and weight gain: a meta‐analytic review

Abstract: Summary According to learning-based models of behavior, food cue reactivity and craving are conditioned responses that lead to increased eating and subsequent weight gain. However, evidence supporting this relationship has been mixed. We conducted a quantitative meta-analysis to assess the predictive effects of food cue reactivity and craving on eating and weight-related outcomes. Across 69 reported statistics from 45 published reports representing 3,292 participants, we found an overall medium effect of food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
419
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 571 publications
(446 citation statements)
references
References 236 publications
(341 reference statements)
22
419
2
3
Order By: Relevance
“…The physiologic preparatory responses (cephalic phase responses) enable the organism to better digest, absorb, and metabolize nutrients (Power & Schulkin, 2008), and overall, appetitive responses motivate the organism to obtain and consume food. In line with this, increased levels of food cue reactivity (e.g., cue-elicited desires to eat) have been associated with overeating, unsuccessful dieting, higher BMI, and eating psychopathology (Boswell & Kober, 2016;Ferriday & Brunstrom, 2011;Ferriday & Brunstrom, 2008;Jansen, 1998;Jansen et al, 2003;Staiger, Dawe, & McCarthy, 2000;van den Akker, Stewart, Antoniou, Palmberg, & Jansen, 2014).…”
Section: Food Cue Reactivity and Pavlovian Conditioningmentioning
confidence: 66%
See 1 more Smart Citation
“…The physiologic preparatory responses (cephalic phase responses) enable the organism to better digest, absorb, and metabolize nutrients (Power & Schulkin, 2008), and overall, appetitive responses motivate the organism to obtain and consume food. In line with this, increased levels of food cue reactivity (e.g., cue-elicited desires to eat) have been associated with overeating, unsuccessful dieting, higher BMI, and eating psychopathology (Boswell & Kober, 2016;Ferriday & Brunstrom, 2011;Ferriday & Brunstrom, 2008;Jansen, 1998;Jansen et al, 2003;Staiger, Dawe, & McCarthy, 2000;van den Akker, Stewart, Antoniou, Palmberg, & Jansen, 2014).…”
Section: Food Cue Reactivity and Pavlovian Conditioningmentioning
confidence: 66%
“…However, this CS+ (but not the CS-) was always accompanied by a picture of the food US. Since food pictures are potent CSs on their own that elicit appetitive responses (Boswell & Kober, 2016), it is impossible to determine whether differential responding was due to presentation of the existing cue (food picture) or due to the newly conditioned cue -i.e., it is unclear whether differential skin conductance responses reflected conditioning effects.…”
Section: Introductionmentioning
confidence: 99%
“…Ultra-processed foods stimulate the brains' reward centre, creating a craving or desire to eat (Boswell and Kober, 2016;Stoeckel et al, 2017). The high availability of less healthy food in the environment also acts as a cue to eat.…”
Section: Food Swampsmentioning
confidence: 99%
“…Jansen, 1998). Indeed, a meta-analysis showed that cue-induced food cravings were prospectively related to eating and weight gain, with similar (medium) effect sizes for children and adults (Boswell & Kober, 2016). Moreover, a pilot study showed that cue reactivity was significantly reduced in successful dieters (formerly obese) compared to unsuccessful (still obese) dieters (A. Jansen, Stegerman, Roefs, Nederkoorn, & Havermans, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…meta-analysis showed that the magnitude of induced cue reactivity (i.e., cue-induced eating desires) is prospectively related to the amount eaten in a laboratory setting and weight, measured both immediately after the cue reactivity manipulation and at longer-term (i.e., one week -two years), with similar (medium) effect sizes for children and adults (Boswell & Kober, 2016). Further, a pilot study compared food cue reactivity between obese dieters and successful dieters who were previously obese, successfully lost weight and maintained the weight loss for half a year.…”
mentioning
confidence: 99%